National Geographic book of nature poetry : more than 200 poems with photographs that float, zoom, and bloom! - Lewis, J. Patrick (National Geographic Society, 2015)
"When words in verse are paired with the awesomeness of nature, something magical happens. Beloved former U.S. Poet Laureate J. Patrick Lewis curates an exuberant poetic celebration of the natural world in this stellar collection of nature poems. From trickling streams to deafening thunderstorms to soaring mountains, discover majestic photography perfectly paired with contemporary (such as Billy Collins), classics (such as Robert Frost), and never-before-published works"--